2007
DOI: 10.1017/s1742758407877459
|View full text |Cite
|
Sign up to set email alerts
|

Relative toxicity of neem to natural enemies associated with the chickpea ecosystem: a case study

Abstract: Neem products are often perceived as harmless to natural enemies, pollinators and other non-target organisms. For this reason, several integrated pest management (IPM) programmes have adopted neem as one of the prime components. This study revealed toxic effects of neem on soil-inhabiting and aerial natural enemies in chickpea to an extent of 41 and 29% population reduction, respectively, compared with 63 and 51% when using a conventional insecticide (endosulfan). Neem also affected the parasitization of Helic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…Observations on the effects of various treatments on soil inhabiting natural enemies at vegetative phase revealed that plots treated with endosulfan had significantly lower populations (107.7 trap −1 ) with 64 % reduction compared to the control (302.3 trap −1 ). The plots treated with HNPV showed minimum disturbance to natural enemies with a catch of 267.1 trap −1 , on par with the control (Ranga Rao et al 2008).…”
Section: Effect Of Ipm Options On Soil Inhabiting Natural Enemiesmentioning
confidence: 93%
See 2 more Smart Citations
“…Observations on the effects of various treatments on soil inhabiting natural enemies at vegetative phase revealed that plots treated with endosulfan had significantly lower populations (107.7 trap −1 ) with 64 % reduction compared to the control (302.3 trap −1 ). The plots treated with HNPV showed minimum disturbance to natural enemies with a catch of 267.1 trap −1 , on par with the control (Ranga Rao et al 2008).…”
Section: Effect Of Ipm Options On Soil Inhabiting Natural Enemiesmentioning
confidence: 93%
“…In the present IPM module, the use of neem during the vegetative phase, followed by the application of Helicoverpa Nucleo Polyhedrosis virus (HNPV), a popular insect pathogen at flowering and needbased application of chitin inhibitors (novaluron, flufenoxuron) instead of conventional insecticide (endosulfan) during pod formation phase in pest management would be of immense help in augmenting the natural enemies in the chickpea ecosystem (Ranga Rao et al 2008). …”
Section: Bio-rationalsmentioning
confidence: 99%
See 1 more Smart Citation
“…HaNPV@ 250 LE ha -1 application on chickpea resulted in a reduction of aerial and soil inhabiting natural enemies by 15 and 22 per cent respectively, over the control plots, while the reduction in the endosulfan sprayed plots was 52.4 and 63.1 per cent, respectively (Ranga Rao et al, 2008).…”
Section: T Chilonismentioning
confidence: 99%
“…Among the leguminous crops chickpea (Cicer arietinum L.) is an important, nutritive and inexpensive crop among the people of the developing world (Sharma et al, 2007). Moreover chickpea plays a key role in increasing soil fertility through biological nitrogen fixation (Rao et al, 2008). From sowing to maturity a number of insect pests attack chickpea plants.…”
Section: Introductionmentioning
confidence: 99%